2014
DOI: 10.3892/mco.2014.302
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DDR2, BRAF, EGFR and KRAS mutations as therapeutic targets in non-adenocarcinoma lung cancer patients

Abstract: Abstract. Molecular-targeted therapy has not been established in non-adenocarcinoma lung cancer (non-AdLC), as no targets that affect the clinical efficacy of molecular-targeted drugs have yet been identified. In this study, we investigated the frequency of genetic variations in discoidin domain receptor 2 (DDR2), v-raf murine sarcoma viral oncogene homolog B1 (BRAF), epidermal growth factor receptor (EGFR) and v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) in non-AdLC patients, in order to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In aseriesof 41 “histologically-pure” LCNECs, which are those tumors that do not contain other histologic components, EGFR and KRAS were evaluated by Sequenom, and 7 samples were found to harbor KRAS mutations. 43 EGFR/KRAS/DDR2/BRAF sequencing was performed in a second series of 11 patients with pure LCNEC, 44 and one KRAS mutation was noted. 44 Importantly, SCLC tumors do not harbor KRAS mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In aseriesof 41 “histologically-pure” LCNECs, which are those tumors that do not contain other histologic components, EGFR and KRAS were evaluated by Sequenom, and 7 samples were found to harbor KRAS mutations. 43 EGFR/KRAS/DDR2/BRAF sequencing was performed in a second series of 11 patients with pure LCNEC, 44 and one KRAS mutation was noted. 44 Importantly, SCLC tumors do not harbor KRAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…43 EGFR/KRAS/DDR2/BRAF sequencing was performed in a second series of 11 patients with pure LCNEC, 44 and one KRAS mutation was noted. 44 Importantly, SCLC tumors do not harbor KRAS mutations. 43,45,46 Furthermore, genomic studies have demonstrated that subsets of LCNECs may harbor other alterations, seen in both adenocarcinomas and even squamous cell lung carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery, chemotherapy, radiotherapy, and targeted therapies are conventional lung cancer treatments [ 3 ]. Targeted therapies with tyrosine kinase inhibitors (TKIs) comprise epidermal growth factor receptor (EGFR) inhibitors, such as erlotinib or gefitinib, and anaplastic lymphoma kinase (ALK) inhibitors, such as crizotinib [ 4 , 5 ]. Considering the high mortality and morbidity rates of lung cancer and the emergence of drug resistance to chemoradiotherapy regimens and TKIs, determining targetable genetic changes is of paramount importance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further evaluations in Korea, China, and France populations revealed that the frequencies of DDR2 mutations were 2%, 4.6%, and 4% in SCC, respectively [ 10 12 ]. However, Kenmotsu et al and Yashima et al did not find any mutations in DDR2 gene of Japanese SCC patients [ 13 , 14 ]. In addition, despite the broader range of mutated genes in SCC, there is no effective targeted treatment for this subtype [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SCC, who comprise about 40% of all NSCLC cases, are very rarely responsive to targeting agents, and specific genetic alterations in SCC have not been identified to date. Recent molecular analyses have identified genes that may play important roles in lung squamous cell tumorigenesis, including FGFR1 , PIK3CA (phosphoinositide-3-kinase catalytic alpha polypeptide), SOX2 , and DDR2 [ 3 , 22 , 23 ]. Tumor cell lines harboring DDR2 mutations have shown increased sensitivity to multiple tyrosine kinase inhibitors in vitro and in vivo , including small molecule inhibitors such as dasatinib, nilotinib, and AP24534 [ 3 , 16 ].…”
Section: Discussionmentioning
confidence: 99%